INDIGENOUS TECHNOLOGIES IN HOME PROCESSING OF ROOT CROPS: A SURVEY AND ECONOMIC ANALYSIS - Alkuino Jr., Jose M.; Van Den, Truong (Annals of Tropical Research, 1989)
This study analyzed the income generating potential of indigenous tech-nologies in processing sweet potato and cassava roots in the rural areas. Twenty-three indigenous root crop processing products were studied and classified as fried, steamed, baked and dried. Of the 23 products monitored, nine have positive net returns namely maruya, bitsu-bitso, cassava doughnut, pilipit, sinaging, pinisi, cacharon, slice and tinitim. The use of inefficient indigenous tools and equipment, unstandardized product formulation and high labor input greatly contributed to the high production cost, hence the losses in the other products.